Pengaruh Media Puzzle terhadap Hasil Belajar Bangun Ruang Siswa Kelas V SDN 1 Timbang: The Influence of Puzzle Media on the Learning Outcomes of Class V Students of SDN 1 Timbang in Spatial Structures - Amallia Nur Pratiwi; Eka Titi Andaryani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to evaluate the effect of implementing puzzle-learning media on spatial geometry material in mathematics on the learning outcomes of fifth-grade students at SD Negeri 1 Timbang. The background of this study is the low students’ ability to understand spatial geometry concepts and the use of conventional learning media, which call for more engaging and concrete learning innovations. This study uses a quasi-experimental Two-Group Posttest-Only Design, with two groups: the experimental group, which received treatment via puzzle-learning media, and the control group, which used cardboard media. The research sample consisted of 34 students, selected using simple random sampling. The data collection methods used include tests, observations, and documentation, supported by instruments that have been tested and declared to meet validity and reliability standards. Data analysis was carried out using prerequisite tests, including tests for normality and homogeneity, followed by hypothesis testing. The results of the study indicate that the use of puzzle media positively influences student learning outcomes across the cognitive, affective, and psychomotor domains. The use of puzzle media in the learning process improves student learning outcomes more than the use of cardboard media. This is likely due to differences in the effectiveness and characteristics of each learning medium. Puzzles can also make abstract concepts more concrete, increase student engagement, and motivate students. Puzzles play a significant role in supporting the learning process. Therefore, implementing puzzles can be considered an effective alternative strategy for improving the quality of mathematics learning in elementary schools.